Politik Islam Era Gus Dur: Antara Mitos dan Realitas - Cipto, Bambang (Unisia, 2016)
Since the based-on religion parlies emerge again in the Indonesia political stageespecially when they succeeded in electing GUS DUR as the president, Moslem society has a very hard consequence. Abdul Rahman Wahid who has a very specific style in solving problems and who in the same time is considered as the protector of the minority becomes a certain dilema figure for Moslems. He brings a hope for moslems to give them more endorsement, but unfortunately GUS DUR is not an easy man to dictate. The writer of this book views that the problem is mainly because of the shackle institution around the presidency as well as GUS DUR's unpredictable political steps. He were standing between the maintenance of democracy in one side and the future of this state in other side.